2021
DOI: 10.1029/2020jd033965
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Water Balance in the Qaidam Basin to the Mid‐Pliocene Climate

Abstract: The Qaidam Basin (QB) in the northeastern Tibetan Plateau held a mega-lake system during the Pliocene. Today, the lower elevations in the basin are hyperarid. To understand to what extend the climate plays a role in the maintenance of the mega-lake system during the Pliocene, we applied the Weather Research and Forecasting model for dynamical downscaling of ECHAM5 global climate simulations for the present day and the mid-Pliocene.When imposing the mid-Pliocene climate on the QB with its modern land surface se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…This finding has later been also demonstrated by Wang, Schmidt, et al. (2021) using dynamical downscaling techniques. They found that specific humidity, precipitation, and net precipitation were higher during the mid‐Pliocene, although air temperature was lower in the mid‐Pliocene over this region.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This finding has later been also demonstrated by Wang, Schmidt, et al. (2021) using dynamical downscaling techniques. They found that specific humidity, precipitation, and net precipitation were higher during the mid‐Pliocene, although air temperature was lower in the mid‐Pliocene over this region.…”
Section: Discussionsupporting
confidence: 75%
“…In regions with complex mountain topography, GCMs' predictions of orographic precipitation may be dry biased due to the GCM smoothing of regional topography (Tselioudis et al., 2012). Dynamic downscaling techniques in conjunction with paleoclimate GCM simulations could help improve precipitation prediction (e.g., Wang, Schmidt, et al., 2021). Furthermore, ECHAM5 tends to underestimate the moisture from the local recycling (Haese et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations